Comparative analysis of paddy cultivation sustainability through integrating eco-efficiency and best-worst method approaches - Mehri Alijani; Yaser Feizabadi; Mostafa Goudarzi (Journal of Agriculture and Food Research)
To investigate the sustainability of agricultural systems, it is necessary to prioritize production systems from various viewpoints. The current research, as a new approach, aimed at prioritizing different paddy cultivation areas in Iran based on sustainability criteria using the best-worst method (BWM), which is regarded as one of the modern multi-criteria decision-making techniques. Mazandaran, Fars, and Khuzestan areas in Iran with different climatic classes, i.e., Mazandaran, Fars, and Khuzestan, were considered in this study. Sustainability criteria included energy, exergy, economic, and environmental indices, and the prioritization process was done based on the eco-efficiency index and BWM method. In the evaluation of the eco-efficiency index, the amount of net income and the total environmental index were considered as economic and environmental indices, respectively. In the prioritization of the BWM method, ranking was done based on energy and exergy efficiency, benefit-cost ratio, and the total environmental index. The results of the eco-efficiency index investigation demonstrated that paddy production in Mazandaran province had the most sustainability and compatibility with the environment, followed by Fars and Khuzestan provinces, respectively. The results of the BWM method prioritization also indicated that Mazandaran province was the best and most sustainable area with a final index of 0.98, followed by Fars and Khuzestan provinces, which were placed in the next ranks of sustainable paddy cultivation areas with final indices of 0.93 and 0.85, respectively. In conclusion, the paddy production systems located in the humid subtropical region were found as the most sustainable systems in this area.